C.K. Averill papers - Averill, C. K.
Two scrapbooks of clippings concerning the Civil War in November 1863 and the political campaigns of 1873-1874. Includes a letter from Averill to Orlando Kellogg, U.S. congressman from New York.
Collection material in English.
Keywords: Kellogg, Orlando, -- 1809-1865 -- Correspondence; Political campaigns; New York (State) -- Politics and government -- 1775-1865.; United States -- History -- Civil War, 1861-1865.